Investigation of the Influence of the Type and Quantity of Structure-Forming Modifiers on the Properties of Heterocomposite Polymer Mixtures used in Railway Transport (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2024)
This article describes the experience of using modern polymer composite materials, as well as the influence of the type and amount of structure-forming modifiers on the properties of heterocomposite mixtures used in the railway industry.